Respuesta :
Answer:
2X/(3+X)
Step-by-step explanation:
X = 3m/2-m
Cross multiply both sides
X × (2-m)= 3m
2X-Xm= 3m
2X= 3m+Xm
2X= m(3+X)
Divide both sides by the coefficient of m which is (3+X)
m= 2X/(3+X)
Changing the subject of a formula involves rearranging the formula
m as the subject of the formula is: [tex]\mathbf{m = \frac{2x}{3 + x}}[/tex]
The equation is given as:
[tex]\mathbf{x = \frac{3m}{2-m}}[/tex]
Cross multiply
[tex]\mathbf{x(2-m) = 3m}[/tex]
Open brackets
[tex]\mathbf{2x-mx = 3m}[/tex]
Collect like terms
[tex]\mathbf{2x= 3m +mx}[/tex]
Factor out m
[tex]\mathbf{2x= m(3 +x)}[/tex]
Divide both sides by 3 + x
[tex]\mathbf{\frac{2x}{3 + x}= m}[/tex]
Rewrite the above equation as:
[tex]\mathbf{m = \frac{2x}{3 + x}}[/tex]
Hence, m as the subject of the formula is:
[tex]\mathbf{m = \frac{2x}{3 + x}}[/tex]
Read more about the subject of formulas at:
https://brainly.com/question/17658928